Kekerasan Baja DC 11 Pada Perlakuan Media Quenching dan Suhu Tempering - Naufal Hanif Fadhlurrohman Aziz; Sulistyono Sulistyono (P3M Politeknik Negeri Cilacap, 2023)
Heat treatment is a process of renewing the metal structure by heating the specimen to a temperature below the melting point and a certain time, which is then cooled in a cooling medium to change the physical and mechanical properties. This study aims to determine the effect of quenching media and tempering temperature on the hardness value of DC 11 steel. This study used an experimental method with hardening at 990 °C and a holding time of 30 minutes with quenching media with SAE 10W-30 oil and 3.45 NaCl solution. %. After that, tempering was carried out at 250 °C, 350 °C, and 450 °C with a holding time of 2 hours. Then, the specimens were tested for hardness using the Rockwell method. Based on the results of the study, it was found that the effect with the highest hardness value was found in the quenching media with 3.45% NaCl solution and a tempering temperature of 250 °C of 49.6 HRC. The conclusion obtained is that the higher the tempering temperature, the lower the hardness value.